Analisis Bentuk dan Fungsi Tuturan Belian Sentiyu pada Masyarakat Muara Begai Kabupaten Kutai Barat - Fitriana, Fitriana; Indrahastuti, Tri; Rijal, Syamsul (Adjektiva: Educational Languages and Literature Studies, 2020)
Belian sentiyu is a traditional ceremony performed by the Dayak Benuaq people in Muara Begai village, West Kutai Regency, East Kalimantan. The ceremony is related to the belief system and religion adopted by the local community and relates to requests for help to the spirits of spirits around them as well as ancestral spirits and the upper rulers (lahtala) and also the lower rulers (uwokng). This research focuses on the form and function of Belian Sentiyu's speech in the Muara Begai community. The purpose of this research was to describe the form and function of Belian Sentiyu's speech in the Muara Begai community. The research method used is descriptive qualitative research method. The data collection techniques used were observation, interview, recording, documentation, transcription, recording and summarizing, and translation techniques. The data analysis technique used is the analysis technique of Lexy J. Moleong, namely data reduction, data presentation, and drawing conclusions. The results obtained from the form of speech in the form of spell characteristics, namely: (a) a series of rhyming words, (b) verbal, magical or magical, (c) espheric (a special language between the speaker and the interlocutor) and mysterious, ( d) use words that are less commonly used in everyday life. The functions of Belian Sentiyu's speech are: (a) as a means of validating cultural institutions and institutions, (b) as a means of educating children, (c) as a means of coercion and control so that the norms of society will always be obeyed by its collective members.